Single‐Particle Cryo‐EM and 3D Reconstruction of Hybrid Nanoparticles with Electron‐Dense Components. Issue 38 (14th July 2015) - Yu, Guimei; Yan, Rui; Zhang, Chuan; Mao, Chengde; Jiang, Wen
<x xml:space="preserve">Abstract</x> Single‐particle cryo‐electron microscopy (cryo‐EM), accompanied with 3D reconstruction, is a broadly applicable tool for the structural characterization of macromolecules and nanoparticles. Recently, the cryo‐EM field has pushed the limits of this technique to higher resolutions and samples of smaller molecular mass, however, some samples still present hurdles to this technique. Hybrid particles with electron‐dense components, which have been studied using single‐particle cryo‐EM yet with limited success in 3D reconstruction due to the interference caused by electron‐dense elements, constitute one group of such challenging samples. To process such hybrid particles, a masking method is developed in this work to adaptively remove pixels arising from electron‐dense portions in individual projection images while maintaining maximal biomass signals for subsequent 2D alignment, 3D reconstruction, and iterative refinements. As demonstrated by the success in 3D reconstruction of an octahedron DNA/gold hybrid particle, which has been previously published without a 3D reconstruction, the devised strategy that combines adaptive masking and standard single‐particle 3D reconstruction approach has overcome the hurdle of electron‐dense elements interference, and is generally applicable to cryo‐EM structural characterization of most, if not all, hybrid nanomaterials with electron‐dense components.